2008
DOI: 10.1097/inf.0b013e318170af5b
|View full text |Cite
|
Sign up to set email alerts
|

Kluyvera Infections in the Pediatric Population

Abstract: In pediatric patients, Kluyvera spp. has emerged as a cause of disease ranging from soft tissue infections to sepsis with multiorgan failure. Successful treatment options include third-generation cephalosporins, tetracycline, aminoglycosides, and fluoroquinolones, but resistance to first- and second-generation cephalosporins persists. Clinicians should be aware of the spectrum of disease and increasing clinical importance associated with this emerging pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It has been reported that three (K. ascorbata, K. cryocrescens, K.georgiana) of the four types demonstrated until the present time cause infection in humans and the most common among these is K. ascorbata as in our patient series (8). While K. ascorbata was isolated in 11 of 19 pediatric patients in the literature and K. cryocrescens was isolated in three, typing could not be done in five (3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In Table 1, all pediatric cases in which Kluyvera infection was reported is summarized.…”
Section: Discussionmentioning
confidence: 70%
“…It has been reported that three (K. ascorbata, K. cryocrescens, K.georgiana) of the four types demonstrated until the present time cause infection in humans and the most common among these is K. ascorbata as in our patient series (8). While K. ascorbata was isolated in 11 of 19 pediatric patients in the literature and K. cryocrescens was isolated in three, typing could not be done in five (3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In Table 1, all pediatric cases in which Kluyvera infection was reported is summarized.…”
Section: Discussionmentioning
confidence: 70%
“…In humans, it is part of the normal flora of the digestive tract. Kluyvera infection is rare but has increasingly been reported [5], such as in children [6].…”
Section: Discussionmentioning
confidence: 99%
“…Kluyvera ascorbata has been implicated as an opportunistic pathogen in neonates . Therefore, to reduce neonatal morbidity and mortality, prompt identification of Kluyvera as the causative agent and use of appropriate antibiotics are mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kluyvera has been associated with clinically significant infections such as urinary tract infection (UTI), bacteremia, and severe sepsis . Of the 15 clinically significant cases of pediatric Kluyvera infection, three cases of fatal infection have been documented, but only a few neonatal cases of Kluyvera infection have been reported …”
mentioning
confidence: 99%